2008
DOI: 10.1007/s00253-008-1363-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of thermostability of fungal deglycating enzymes by directed evolution

Abstract: Fructosyl peptide oxidases are valuable for the determination of glycoproteins such as hemoglobin A1c. For practical use in clinical diagnosis, we applied directed evolution to improve the thermostability of these enzymes. After two rounds of random mutagenesis and high-throughput screening, six thermostabilizing amino acid substitutions were identified. Therefore, site-directed and cassette mutageneses were applied to combine these six stabilizing mutations. The simultaneous mutants showed that the stabilizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Interestingly, analysis of the intramolecular interactions showed that while some mutants exhibited increased molecular interactions with stabilizing effects, the thermal tolerance of the enzyme was enhanced with the E124I and S271G substitutions, which eliminated several ion pairs or hydrogen bonds; this observation cannot be explained based on our current understanding of the enzyme and enzyme structure (48,50,51). The stabilizing effects of point mutations can be cumulative (27,42,45,47). Indeed, in our study, some further-improved combined mutants were also obtained.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Interestingly, analysis of the intramolecular interactions showed that while some mutants exhibited increased molecular interactions with stabilizing effects, the thermal tolerance of the enzyme was enhanced with the E124I and S271G substitutions, which eliminated several ion pairs or hydrogen bonds; this observation cannot be explained based on our current understanding of the enzyme and enzyme structure (48,50,51). The stabilizing effects of point mutations can be cumulative (27,42,45,47). Indeed, in our study, some further-improved combined mutants were also obtained.…”
Section: Discussionmentioning
confidence: 61%
“…Although successful approaches for improving the thermostability of pectin hydrolysis enzymes have been reported (27,42,44), improvement of thermostability by protein engineering is still challenging. Directed evolution is a widely used technique for protein engineering in which proteins are improved through iterative cycles of diversity generation and screening; this method has been successfully carried out for various enzymes to improve their thermostability or catalytic activity (27,(45)(46)(47). In this study, BspPelA was successfully engineered by directed-evolution strategies, including random mutagenesis and SSM, in order to improve its thermostability and catalytic efficiency for degumming of ramie fibers.…”
Section: Discussionmentioning
confidence: 99%
“…To generate more thermostable mutants of ChKRED20, we subsequently applied combinations of beneficial mutations for possible synergistic or additive effect (Giver et al 1998;Hirokawa et al 2008;McLachlan et al 2008;Pei et al 2011;Zhang et al 2012). After the generation of several double, triple, and quadruple mutants, their residual activities were measured after heat treatment at 70°C for 3 h using the crude enzyme extracts (Fig.…”
Section: Combination Of Beneficial Mutationsmentioning
confidence: 99%
“…N1-1 (Tsugawa et al 2000). Site-directed mutagenesis studies of FAODs have been extensively carried out aiming at the alteration of substrate specificity (Fujiwara et al 2006(Fujiwara et al , 2007Miura et al 2008;Kim et al 2009) and also to improve their stability (Sakaue and Kajiyama 2003;Hirokawa et al 2008). However, no attempt has ever been reported on the improvement of their electron acceptor availability.…”
Section: Introductionmentioning
confidence: 99%